2016
DOI: 10.5194/adgeo-42-61-2016
|View full text |Cite
|
Sign up to set email alerts
|

Can small pelagic fish landings be used as predictors of high-frequency oceanographic fluctuations in the 1–2 El Niño region?

Abstract: Abstract. A group of small pelagic fish captured between 1981 and 2012 within El Niño area 1–2 by the Ecuadorian fleet was correlated with the oceanographic Multivariate ENSO Index (MEI), and the Oceanographic El Niño Index (ONI) referred to El Niño region 3–4. For the period 1981–2012, total landings correlated poorly with the indexes, but during 2000–2012 (cold PDO) they proved to have a 14–29 % association with both indexes; the negative slope of the curves suggested higher landing during cold events (La Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In terms of a larger time scale index, such as the PDO, there is uncountable evidence that tuna fish biomass is at higher levels when the PDO is on cold phase (2000-2030). Ormaza-González et al (2016) have found the length and weight of Opisthonema spp (a type of sardine fish called "pinchagua") have a higher linear correlation up to 40 % to MEI and ONI indexes when data for the fourth quarter of the year was analyzed in time series 2000-2012 of these indexes. Similar outcomes where found when using small pelagic fish correlated to cold phase PDO (Ormaza-González et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of a larger time scale index, such as the PDO, there is uncountable evidence that tuna fish biomass is at higher levels when the PDO is on cold phase (2000-2030). Ormaza-González et al (2016) have found the length and weight of Opisthonema spp (a type of sardine fish called "pinchagua") have a higher linear correlation up to 40 % to MEI and ONI indexes when data for the fourth quarter of the year was analyzed in time series 2000-2012 of these indexes. Similar outcomes where found when using small pelagic fish correlated to cold phase PDO (Ormaza-González et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Ormaza-González et al (2016) have found the length and weight of Opisthonema spp (a type of sardine fish called "pinchagua") have a higher linear correlation up to 40 % to MEI and ONI indexes when data for the fourth quarter of the year was analyzed in time series 2000-2012 of these indexes. Similar outcomes where found when using small pelagic fish correlated to cold phase PDO (Ormaza-González et al, 2016). The analysis of the CPUE suggests that fishermen and managers would expect higher CPUE on FADs around 20 mt set −1 when indexes are below -0.5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Explicably, the oil sardine catch and catch rates were negatively correlated with MEI and the relative importance model showed that MEI was the most important parameter explaining the variance (33%), thus indicating that the El Niño had negatively affected the sardine stock and its fisheries. In the round herring (Etrumeus teres) fishery in Ecuador, landings were related to the MEI in a nonlinear analysis by up to 80% (Ormaza-González et al, 2016). Among the different factors affecting spawning and recruitment of anchoveta populations, El Niño has been reported as the most striking (Checkley et al, 2009).…”
Section: Impact Of El Niño/southern Oscillation -Ensomentioning
confidence: 99%
“…Environmental impact is huge in terms of diluvial rain episodes [3], release of gases to the atmosphere as their solubility decreases because the sea surface temperature (SST) increases nutrient depletion [4] and reduction of photosynthesis [5]. The whole marine trophic chain is negatively affected: this include important fish stocks as small and big pelagic fish [6,7]. El Niño [8,9] is a relatively low frequency (inter-annual) and non-cycled oceanographicatmospheric coupled process whose definition is referred to the area Niño 3.4 ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%